Head-mounted display versus desktop for 3D navigation in virtual reality: A user study - Sousa Santos, B. (2009)
Virtual Reality (VR) has been constantly evolving since its early days, and is now a fundamental technology in different application areas. User evaluation is a crucial step in the design and development of VR systems that do respond to users' needs, as well as for identifying applications that indeed gain from the use of such technology. Yet, there is not much work reported concerning usability evaluation and validation of VR systems, when compared with the traditional desktop setup. The paper presents a user study performed, as a first step, for the evaluation of a low-cost VR system using a Head-Mounted Display (HMD). That system was compared to a traditional desktop setup through an experiment that assessed user performance, when carrying out navigation tasks in a game scenario for a short period. The results show that, although users were generally satisfied with the VR system, and found the HMD interaction intuitive and natural, most performed better with the desktop setup.